Cause-related marketing in South Africa : effects of donations and rewards on consumers’ perceived motives, perceived fairness, attitudes and purchase intention - Van Schoor, Mari-Lu (Stellenbosch : Stellenbosch University, 2021)
Thesis (MCom)--Stellenbosch University, 2021.